Improving Reading Skills and Engagement in Pancasila Education Using QR-Code-Assisted Snowball Throwing Method - Ummah, Salsa Sayyidatul; Aeni, Kurotul (International Journal of Elementary Education, 2024)
The selection of inappropriate and uncreative teaching tools can reduce students' interest in reading, leading to difficulties in understanding material in Pancasila Education. This study aims to analyze the effectiveness and differences of the Snowball Throwing method assisted by QR-Code within the Problem-Based Learning model in improving elementary students' reading skills and interest. This research adopts a quantitative approach using a quasi-experimental design, specifically a Non-Equivalent Control Group Design. The study sample comprised 43 fifth-grade students, with 22 students in the experimental group and 21 students in the control group. Data were collected through interviews, observations, tests (pretest and posttest), and questionnaires. Data analysis included normality and homogeneity tests as prerequisites, as well as Independent t-test and N-Gain tests to test the hypotheses. The findings reveal that the Snowball Throwing method assisted by QR-Code within the Problem-Based Learning model is effective in improving students' reading skills and interest. Furthermore, there is a significant difference between this method and conventional teaching methods, with the innovative model demonstrating better outcomes in Pancasila Education learning. In conclusion, this method offers a creative alternative to enhance the quality of education in elementary schools.